Ophiopogon japonicus inhibits white spot syndrome virus proliferation in vivo and enhances immune response in Chinese mitten crab Eriocheir sinensis. Issue 119 (December 2021) - Chen, Cheng; Shen, Jing-Lei; Wang, Tao; Yang, Bin; Liang, Chang-Shuai; Jiang, Hai-Feng; Wang, Gao-Xue
Abstract: White spot syndrome virus (WSSV) is a fatal pathogen threatening global crustacean industry with no commercially available drugs to control. Herbal medicines have been widely used to treat a number of viral infections, which could offer a rich reserve for antiviral drug discovery. Here, we evaluated the inhibition activities of 30 herbal medicines against WSSV in Chinese mitten crab Eriocheir sinensis . A WSSV infection model in E. sinensis was firstly established in order to determine the antiviral effects of the plant extracts and to explore the potential action mechanisms. Results showed that the highest anti-WSSV activity was obtained by the treatment of Ophiopogon japonicus extract (93.03%, 100 mg/kg). O. japonicus treatment decreased viral loads in a dose-dependent manner and significantly improved the survival of WSSV-challenged crabs. O. japonicus reduced the expression of vital genes in viral life cycle in vivo, particularly for the immediate-early stage gene ie1 . Further results indicated that O. japonicus could repress the JAK-STAT signaling pathway to block ie1 transcription. Moreover, O. japonicus could modulate certain immune genes such as the myosin, toll-like receptor, crustin, and prophenoloxidase in the interactions between WSSV and crabs. The up-regulated expression of pro-autophagic factors ( Gabarap and Atg7 ) and elevated levels of antioxidant enzymes (SOD, CAT and GSH) suggested that O. japonicus may induce autophagy and attenuate WSSV-induced oxidative stress. Taken together, O. japonicus could inhibit WSSV proliferation and improve the survival of WSSV-challenged crabs. Thus, O. japonicus may have the potential to be developed as a preventive or therapeutic agent against WSSV, and its effective compounds merit further isolation and identification. Highlights: The WSSV infection model was established and evaluated in Eriocheir sinensis for the first time. Ophiopogon japonicus restrains WSSV proliferation and improves survival of WSSV-challenged crabs. O.japonicus represses the JAK/STAT signaling pathway to block the transcription of WSSV early gene. Ophiopogon japonicus induces immune response in crabs. O.japonicus induces apoptosis-related factors and enhances anti-oxidative activity in WSSV-challenged crabs.